Neurological Manifestations Related to Immune Checkpoint Inhibitors: Reverse Translational Research by Using the European Real-World Safety Data - Ruggiero, Rosanna; Stelitano, Barbara; Fraenza, Federica; di Mauro, Gabriella; Scavone, Cristina; Sportiello, Liberata; Rafaniello, Concetta; Di Napoli, Raffaella; Danesi, Romano; Del Re, Marzia; Rossi, Francesco; Capuano, Annalisa (Frontiers in Oncology, 2022)
Immune checkpoints inhibitors (ICIs) are widely used improving clinical outcomes in many cancer patients. However, they can induce serious consequences, like neurological immune-related adverse drug reactions (NirADRs). Although these are rare complications, they can be serious with importa impact on patients' quality of life. Our purpose is to describe these adverse events observed in the European clinical practice context. We carried out a descriptive analysis of individual case safety reports (ICSRs) related to ICIs collected until February 7th, 2020 in the European spontaneous reporting database, Eudravigilance, and reporting nervous disorders reported as suspect ADR. NirADRs were classified according to the Medical Dictionary for Regulatory Activities (MedDRA). In order to identify an hypothetical different reporting probability of the NirADRs types between the ICIs classes, we carried out a disproportionality analysis. The reporting odds ratio (ROR) with 95%CI was computed comparing the different ICIs classes to each other’s based on their pharmacological target (anti-PD1 vs anti-PDL1 vs anti-CTLA4). Finally, we researched in literature the hypothesized mechanisms, which could explain the onset of these ICI-related neurological complications. Overall, we found 4875 cases describing 6429 ICI-related suspected NirADRs. ICIs-related neurotoxicities include a wide range of central and peripheral events. These were mainly related to antiPD-1 agents and occurred in male patients (59%). Our analysis confirmed a gender difference of NirADRs. The 23% of the events (comprising myasthenia gravis, neuropathy peripheral and cerebral infarction) had unfavourable fallouts, including fatal outcome (7%). Majority of the NirADRs were categorized as “Neurological disorders NEC” HLGTs MedDRA (2076; 32%). In 1094 cases (22%) more NirADRs were overlapped with other neurologic complications. An interesting overlapping of myasthenia gravis with myositis or myocarditis emerged. From our disproportionality analysis resulted an increased reporting probability of peripheral neuropathies and headaches with ipilimumab compared to anti-PD1 and anti-PDL1 agents. Instead, the neuromuscular disorders were more probably reported with anti-PD1. Several pathogenic mechanisms, including neuronal damage by T-cells, autoantibodies and/or cytokine-mediated inflammation processes, have been hypothesized. However, the pathogenesis of these ICI-related complications is not completely understood. Considering the recent marketing authorizations of ICIs, further studies are strongly needed to evaluate their neurologic safety profile.